2017
DOI: 10.1002/ffj.3401
|View full text |Cite
|
Sign up to set email alerts
|

Volatile profiles of the orpines roots: Hylotelephium telephium (L.) H. Ohba, H. maximum (L.) Holub and H. spectabile (Boreau) H. Ohba x telephium (L.) H. Ohba

Abstract: The family of succulent plants, Crassulaceae, is known for many benefits, as well for the limited distribution of aromatic representatives. It is also observed the deficiency of data on content and distribution of volatile compounds within the genus Hylotelephium. Accordingly, this is the first report on volatiles from roots of three Hylotelephium taxa: H. telephium, H. maximum and H. spectabile x telephium. Two types of volatiles were isolated: headspace (HS) volatiles and solvent extract volatiles from the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Phytochemical research of the leaves and flowers of this species has shown that it is potentially a good resource of anti-oxidative substances (the flowers are a better source of antioxidants than its leaves). Stojanović et al (2014) showed that, due to the presence of antioxidative substances in the leaf, the ethyl acetate fraction exhibits moderate bactericidal activity against P. aeruginosa, Salmonella typhimurium, S. aureus, and Bacillus subtilis.…”
Section: Quantitative Ethnobotanical Analysesmentioning
confidence: 98%
“…Phytochemical research of the leaves and flowers of this species has shown that it is potentially a good resource of anti-oxidative substances (the flowers are a better source of antioxidants than its leaves). Stojanović et al (2014) showed that, due to the presence of antioxidative substances in the leaf, the ethyl acetate fraction exhibits moderate bactericidal activity against P. aeruginosa, Salmonella typhimurium, S. aureus, and Bacillus subtilis.…”
Section: Quantitative Ethnobotanical Analysesmentioning
confidence: 98%
“…Headspace sampling, GC-MS analysis and identification of volatiles were done in accordance with already published procedure 9 . Sample preparation for analysis was done immediately on opening the bags, by measuring the spice into 20-mL headspace vials and subsequently adding 1 mL of distilled water (AM (g) assigns average mass of samples taken for headspace analysis, Table I).…”
Section: Headspace Sampling Gc-ms/fid Analysis and Identificationmentioning
confidence: 99%
“…There are studies that considered both headspace and essential oil volatiles. In general, the chemical composition of headspace volatiles differs from that of hydrodistillated oil regarding the content of more volatile monoterpene fraction [7][8][9] . Finally, a recent study has demonstrated that headspace sampling is applicable in the quality assessment of sage essential oil as a complementary extraction technique for rapid screening 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Some Hylotelephium species are consumed fresh (leaves) or cooked (leaves, roots). In traditional medicine various species of the genus Hylotelephium are used for skin diseases treatment, such as burns, pimples, wounds, as well as in anti-inflammatory and analgesic treatments [1][2][3]. The distribution of alkaloids is generally limited within the genus Sedum L. (Sedum acre-group); Several types of alkaloids have been identified -pyrrolidines and piperidines (2-monosubstituted and 2,6-disubstituted), which were considered in previous chemotaxonomic studies [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of alkaloids is generally limited within the genus Sedum L. (Sedum acre-group); Several types of alkaloids have been identified -pyrrolidines and piperidines (2-monosubstituted and 2,6-disubstituted), which were considered in previous chemotaxonomic studies [4,5]. Phytochemical studies on the genus comprise several classes of secondary metabolites distributed in different plant organs: flavonoids, glucosides tannins, alkaloids, terpenes, lactones, organic acids, and polysaccharides [2,[6][7][8][9][10][11]. According to published data, extracts of the studied Hylotelephium species showed several biological activities: high antioxidant and anti-inflammatory activity of H. erythrostictum aerial parts extract; antimicrobial and antioxidant activity of leaf and flower extracts, fractions and hydrolysates of H. spectabile x telephium; anti-inflammatory and analgesic activity of the H. kamtschaticum methanol extract [1,12].…”
Section: Introductionmentioning
confidence: 99%